Socio-demographic characteristics of patients with negative and positive symptoms in schizophrenia - Kushnir , Yu.A. (Medicni Perspektivi, 2024)
Schizophrenia is a severe mental disorder that leads to impaired social adaptation, interpersonal interaction, and disability. Negative symptoms are an integral part of schizophrenia. In the world psychiatric science and practice, there are still many questions about the typology of schizophrenia, the description of its clinical manifestations, first of all, the features of negative symptoms in schizophrenia. Psychiatrists of different countries draw attention to the fact that these descriptions do not always coincide. Socio-demographic factors can be considered as factors affecting the prognosis of the course and outcome of schizophrenia. In this regard, a comprehensive approach to the study of socio-demographic characteristics of patients with schizophrenia involves the study of the influence of social factors on the formation and course of schizophrenia and determines the relevance of this study. The purpose of the study was to determine the features of socio-demographic characteristics of patients with schizophrenia in order to improve diagnosis and create psycho-corrective measures. 252 patients with negative symptoms of schizophrenia and 79 patients with positive symptoms of schizophrenia were examined. During the research, a comprehensive approach was used, consisting in the use of clinical-psychopathological, clinical-anamnestic and statistical research methods. Socio-demographic features of patients with negative symptoms in schizophrenia were established, consisting in the predominance of women; patients aged 20-29 years; persons with special secondary education; divorced and single persons; patients busy with physical labor; average level of material wealth; very poor and poor living conditions. Socio-demographic characteristics of patients with positive symptoms in schizophrenia were outlined by the predominance of men; patients aged 30-49 years; persons with incomplete higher education and with higher education; divorced and single persons; patients with disabilities; with extremely low and low levels of material well-being and a satisfactory level of living conditions. The conducted research made it possible to draw conclusions that socio-demographic features of patients with negative and positive symptoms have their own specificity, which should be taken into account when diagnosing patients with schizophrenia.